2010
DOI: 10.1071/mf08296
|View full text |Cite
|
Sign up to set email alerts
|

Effects of an anti-salt intrusion dam on tropical fish assemblages

Abstract: Following the construction of an anti-salt intrusion dam in Pak Panang River, Thailand, changes in the environmental conditions and fish assemblages were monitored both in the estuary and in the river. The present study was conducted during two different phases: when the sluices were open; and when they were closed. Salinity in the estuary declined (P < 0.001), but increased in the river during the open phase (P = 0.002). In the river, the pH increased (P < 0.001) during the closed phase, but was relativ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2011
2011
2024
2024

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 8 publications
(3 citation statements)
references
References 30 publications
0
3
0
Order By: Relevance
“…Saltwater intrusion is a major concern commonly found in estuaries around the world, therefore, several authors have been discussed the environmental impacts of saltwater intrusion in different estuaries, Such as [4][5][6][7][8][9] or on fish assemblages that inhabit coastal rivers, Such as [10][11][12][13].…”
Section: Introductionmentioning
confidence: 99%
“…Saltwater intrusion is a major concern commonly found in estuaries around the world, therefore, several authors have been discussed the environmental impacts of saltwater intrusion in different estuaries, Such as [4][5][6][7][8][9] or on fish assemblages that inhabit coastal rivers, Such as [10][11][12][13].…”
Section: Introductionmentioning
confidence: 99%
“…Among the species caught, only one taxon exhibits true diadromy, the giant prawn Macrobrachium soenbergii . The remaining taxa are amphidromous species or marine visitors, entering the bay mostly for feeding [ 12 , 37 , 38 ]. Soe et al [ 39 ] reported that the fishes of the inner bay community tend to be plankton feeders, meanwhile the community in the outer bay is dominated by piscivores.…”
Section: Discussionmentioning
confidence: 99%
“…This is likely because secondary freshwater fishes were not moving near the bottom and being caught by traps, whereas gillnets capture some secondary freshwater fishes when a high volume of freshwater is discharged into the Bay [ 14 ]. It is unfortunate that there were no samples from December, since it was expected to yield a different cluster showing high %O of secondary freshwater fishes, as experienced in the nearby Pak Panang Bay during the peak of the northeast monsoon (NEM) period, i.e., December to January [ 37 , 38 ]. Cluster C was composed of samples from late NEM to the first monsoon transition (i.e., from February to April), when water temperature was rising.…”
Section: Discussionmentioning
confidence: 99%